THE INFLUENCE OF AUDIT TENURE, TASKS COMPLEXITY, TIME BUDGET PRESSURE, AND AUDIT SPECIALIZATION ON AUDIT QUALITY - Kadek Dina Heryanti; I Made Pande Dwiana Putra (Adisam Publisher, 2024)
The aim of this research is to examineKnow the influence of audit tenure, task complexity, time budget pressure, and audit specialization on audit quality. This research was conducted at all Public Accounting Firms in Bali registered in the directory of the Indonesian Institute of Public Accountants (IAPI) in 2023 with a population of 126 auditors. The sampling technique used was purposive sampling technique and the number of samples obtained was 63 samples of auditors in 19 public accounting firms. Data collection was carried out by distributing questionnaires using a 4 point Likert scale to measure 31 question items. The data analysis technique used is multiple linear regression. Based on the results of the analysis, it was found that audit tenure and specialization had a positive effect on audit quality and had a positive effect on audit quality at the Bali Province Public Accounting Firm. Task complexity and time budget pressure have a negative effect on audit quality at the Bali Province Public Accounting Firm.